Two stage capacitated facility location problem: Lagrangian based heuristics - Litvinchev, Igor; Mata, Miguel; Ozuna, Lucero; Saucedo, Jania; Rangel, Socorro [UNESP] (My University, 2012)
In the two-stage capacitated facility location problem, a single product is produced at some plants in order to satisfy customer demands. The product is transported from these plants to some depots and then to the customers. The capacities of the plants and depots are limited. The aim is to select cost minimizing locations from a set of potential plants and depots. This cost includes fixed cost associated with opening plants and depots, and variable cost associated with both transportation stages. In this work two different mixed integer linear programming formulations are considered for the problem. Several Lagrangian relaxations are analyzed and compared, a Lagrangian heuristic producing feasible solutions is presented. The results of a computational study are reported. © 2013, IGI Global.